Momelotinib long-term safety and survival in myelofibrosis: integrated analysis of phase 3 randomized controlled trials - Verstovsek, Srdan; Mesa, Ruben; Gupta, Vikas; Lavie, David; Dubruille, Viviane; Cambier, Nathalie; Platzbecker, Uwe; Hus, Marek; Xicoy, Blanca; Oh, Stephen T; Kiladjian, Jean-Jacques; Vannucchi, Alessandro M; et al. (Blood advances, 2023)
Momelotinib is the first inhibitor of Janus kinase 1 (JAK1) and JAK2 shown to also inhibit activin A receptor type 1 (ACVR1), a key regulator of iron homeostasis, and has demonstrated improvements in splenomegaly, constitutional symptoms, and anemia in myelofibrosis (MF). This long-term analysis pooled data from 3 randomized phase 3 studies of momelotinib (MOMENTUM, SIMPLIFY-1, and SIMPLIFY-2), representing MF disease from early (JAK inhibitor-naive) to late (JAK inhibitor-experienced) stages. Patients in the control arms (danazol in MOMENTUM, ruxolitinib in SIMPLIFY-1, and best available therapy in SIMPLIFY-2) could cross over to receive momelotinib at the end of the 24-week randomized period, and all patients could continue momelotinib treatment after the completion of these studies via an extended access protocol (XAP). Across these studies, 725 patients with MF received momelotinib; 12% remained on therapy for ≥5 years, with a median treatment exposure of 11.3 months (range, 0.1-90.4 months). The most common nonhematologic treatment-emergent adverse event (AE) occurring in ≥20% of patients was diarrhea (any grade, 27% and grade ≥3, 3%). Any-grade thrombocytopenia, anemia, and neutropenia occurred in 25%, 23%, and 7% of patients, respectively. The most common reason for momelotinib discontinuation was thrombocytopenia (4% discontinuation rate). The incidence of AEs of clinical importance (eg, infections, malignant transformation, peripheral neuropathy, and hemorrhage) did not increase over time. This analysis of one of the largest randomized trial databases for a JAK inhibitor to date in MF demonstrated a consistent safety profile of momelotinib without long-term or cumulative toxicity. These trials were registered at www.clinicaltrials.gov as: MOMENTUM (#NCT04173494), SIMPLIFY-1 (#NCT01969838), SIMPLIFY-2 (#NCT02101268), and XAP (#NCT03441113).
Keywords: primární myelofibróza; Thrombocytopenia; Protein Kinase Inhibitors; trombocytopenie; Janus Kinase Inhibitors; inhibitory Janus kinas; Humans; Anemia; inhibitory proteinkinas; lidé; Randomized Controlled Trials as Topic; Primary Myelofibrosis; randomizované kontrolované studie jako téma; anemie